Agro-entrepreneurs Digital Marketing Awareness Program Among Youth of Kuala Penyu Sabah, Malaysia - Mat Salleh Ayub; Suddin Lada; Arif Kamisan Pusiran (IMPACTS: International Journal of Empowerment and Community Services, 2023)
Purpose - The Community Project’s major goal is to increase awareness of the importance of agriculture-based entrepreneurship (Agro-entrepreneurship). The initiative also aims to foster entrepreneurship among local Sabahan, especially in digital marketing technology. Methods – Conducting workshops and training sessions on agro-entrepreneurship to help educate existing and potential entrepreneurs on the best practices, techniques, and skills required to establish and run successful agro-businesses. Simultaneously, show them how to advertise their products online. This programme comprises two stages of implementation, each with 30 participants and four facilitators. Result and discussions – Agro-entrepreneurs should learn and use strategies for digital marketing by receiving training. Agro-entrepreneurs could reach more clients by using digital marketing methods including social media, email, and content marketing. Agro-entrepreneurs could build and maintain their businesses by using digital marketing. Conclusion – In principle, the awareness programme would have assisted agro-entrepreneurs in improving their knowledge of digital marketing as well as their digital marketing abilities, which would have enabled them to expand their businesses and keep them going over the long term.